MANAJEMEN PEMBELAJARAN DALAM PERSPEKTIF TOTAL QUALITY MANAGEMENT (TQM) DI SD ISLAM TERPADU AL FURQAN AMBAL KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims to describe the overview of the learning management in the perspective of Total Quality Management (TQM) in Al Furqan Integrated Islamic elementary School, Ambal Kebumen Regency.To achieve these objectives, qualitative research method was used. The selection of the research informen determined by using purposive sampling. In his research, the principal and teachers were the key informen. The data were collected by interview, observation, and document assessment. Data were analyzed using qualitative data analysis techniques, namely by organizing data by category, grouped, be numbered according to the chronology of the acquisition / data sources. . The validity of the data is done by continuous observation and triangulation of sources and methods.The results of this research show that: 1).the pattern of learning management in Al Furqan Integrated Islamic Elementary School Ambal Kebumen Regency has applied the perspective of TQM in terms of improving school quality and be able to fullfil the various needs of the students because of learning oriented model of consumer satisfaction that is learners as he consumers of education. 2). The lerning management Al Furqan Integrated Islamic Elementari School, in terms of lesson planning, organizing learning activities, the implementation of learning, learning evaluation, supervision and follow up research are involving all of the school components. Researcher recommended that the Al Furqan Integrated Islamic Elementary should implement the TQM management model, to improve the performance of school administrators and the learning capability of of the students.